Daya Simpan Ikan Bandeng (Chanos Chanos F.) MenggunakanKombinasi Daun Salam (Eugenia Polyantha, Weight.) Dan GaramDengan Lama Perendaman Yang Berbeda - Pamulatsih, Retno; , Dra. Hariyatmi, M.Si; , Ibu Triastuti Rahayu, S.Si, M.Si (2016)
Fish is a fish of high economic value and become a commodity cultivation for a savory flavor and prices can be affordable by the community, but the fish susceptible to damage caused by bacteria, yeasts and fungi. Fish will be damaged if left at room temperature for 12 hours. Bay leaves contain several compounds such as essential oils, tannins and flavonoids, which are anti microorganisms, so it can be used as a natural preservative. The aim of research to determine the shelf life of fish are preserved using bay leaves and salt with different soaking time. This research method using a completely randomized design (CRD) two factors, one that is preservative solutions (P0 = distilled water as a control, P1 = bay leaves 24% + salt 4,8%) and factor 2 is long immersion (K1 = 60 minutes, K2 = 90 min) with 4 treatments. The results of the research that the best quality fish preservation is in treatment P1K2 (bay leaves 24% + 4,8% salt by soaking 90 minutes) on the hour to 6 with the number of bacteria as much as 1.90 x 1010 cfu / g. The physical condition of the fish on the P1K2 treatment better than other treatments slime layer clear, sunny and still smelled neutral, meat texture rather soft, if the former is pressed quickly disappear. At all 12 conditions the fish unfit for consumption.